T3P- A Novel Catalyst for Aza-Diels-Alder Reaction: One-Pot Synthesis of Pyrano[3,2-c]quinolines and furano[3,2-c]quinolines - T. S. R. Prasanna; K. Mohana Raju (E-Journal of Chemistry)
T3P was found to be an efficient catalyst for the Aza-Diels–Alder reactions of aldimines with dihydropyran or dihydrofuran to afford the corresponding pyrano-and furo [3,2-c]quinolines in high yields with high diastereoselectivity in a short period of time.